Comparing individual and group intervention for psychological adjustment in people with multiple sclerosis: a feasibility randomised controlled trial - das Nair, Roshan; Kontou, Eirini; Smale, Kathryn; Barker, Alex; Lincoln, Nadina (SAGE, 2015)
Objective